2016
DOI: 10.1001/jamadermatol.2015.4356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofMITFp.E318K in Patients With Melanoma Independent of the Presence ofCDKN2ACausative Mutations

Abstract: The main high-penetrance melanoma susceptibility gene is CDKN2A, encoding p16INK4A and p14ARF. The gene MITF variant p.E318K also predisposes to melanoma and renal cell carcinoma. To date, the prevalence of MITF p.E318K and its clinical and phenotypical implications has not been previously assessed in a single cohort of Spanish patients with melanoma or in p16INK4A mutation carriers. OBJECTIVES To evaluate the prevalence of MITF p.E318K in Spanish patients with melanoma and assess the association with clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 40 publications
9
54
6
Order By: Relevance
“…The MITF p.E318K variant was identified in three additional cases (two families and one patient). The occurrence (7%) of this variant among families is higher than reported previously for other populations . Also, contrary to what has been reported, no kidney cancer was detected in these three families.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The MITF p.E318K variant was identified in three additional cases (two families and one patient). The occurrence (7%) of this variant among families is higher than reported previously for other populations . Also, contrary to what has been reported, no kidney cancer was detected in these three families.…”
Section: Discussioncontrasting
confidence: 94%
“…4,6,14 Recently, some studies have implicated the BRCA1-associated protein 1 gene (BAP1) and the microphthalmia-associated transcription factor gene (MITF) as high-and intermediate-penetrance melanoma predisposition genes, respectively. [16][17][18][19] Germline BAP1 mutations are associated with a novel cancer syndrome characterized by an increased risk of malignant mesothelioma, atypical melanocytic tumours (melanocytic BAP1-mutated atypical intradermal tumours), uveal and cutaneous melanoma and other neoplasms. 17 The MITF mutation p.E318K is associated with both familial and sporadic melanoma susceptibility and/or renal cell carcinoma risk, an increased naevus count and nonblue eye colour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IRF4 activates the melanogenesis pathway by the regulation of TYR expression, together with MITF. This could be one explanation of why these genes are both implicated in nevi count . It has been suggested that IRF4 expression enables suppressive regulatory T cells (Treg) to suppress effector T cells .…”
Section: Discussionmentioning
confidence: 99%